2014 25th International Workshop on Database and Expert Systems Applications 2014
DOI: 10.1109/dexa.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

Toward Efficient Variant Calling Inside Main-Memory Database Systems

Abstract: Abstract-Mutations in genomes indicate predisposition for diseases or effects on efficacy of drugs. A variant calling algorithm determines possible mutations in sample genomes. Afterwards, scientists have to decide about the impact of these mutations. Certainly, many different variant calling algorithms exist that generate different outputs due to different sequence alignments as input and parameterizations of variant calling algorithms. Thus, a combination of variant calling results is necessary to provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The work of Dorok et al [4] is closest related to our work. It uses a column oriented main memory DBMS to perform in-database variant calling using simple SQL.…”
Section: Related Workmentioning
confidence: 69%
See 1 more Smart Citation
“…The work of Dorok et al [4] is closest related to our work. It uses a column oriented main memory DBMS to perform in-database variant calling using simple SQL.…”
Section: Related Workmentioning
confidence: 69%
“…Moreover, a bigger part of genetic analyses pipeline should be natively supported by MonetDB/BAM. For example, supporting a base-oriented database schema as described by Dorok et al [4], and building in support for loading reference and/or index files, enables users to run in-database variant calling algorithms. Furthermore, implementing indatabase support for VCF files eliminates yet another part of the genetic analyses pipeline that is normally file-based.…”
Section: Future Workmentioning
confidence: 99%
“…In our previous work, we chose the Feb2013-SP2 release of MonetDB to evaluate the query and analysis performance of our approach [10]. We extended MonetDB with a handwritten user-defined aggregation function to support variant calling.…”
Section: Querying and Storing Genome Datamentioning
confidence: 99%
“…First results on variant calling indicate that an integration of genome analysis tasks into a main-memory DBMS is feasible and can be beneficial regarding performance [5].…”
Section: Addressing Data-management Challengesmentioning
confidence: 99%
“…Such dictionary encoding scheme can be efficiently applied to column-stores [1] that are often used in main-memory DBMSs. In recent work, we have shown that DNA sequencing reads can be efficiently compressed using compression schemes such as dictionary encoding [5].…”
Section: A U T H O R ' S V E R S I O Nmentioning
confidence: 99%